EFFECT OF BODY CONDITION SCORE ON MILK YIELD AND COMPOSITION OF BOKANI DAIRY COWS - Izzadeen, Shireen. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The study was conducted on the Erbil Dairy Herd of the Erbil city, to evaluate the effect of body condition score of Bokani dairy cow on milk composition. Milk samples were examined weekly for milk yield and milk fat, protein percentage, fat / protein ratio, lactose, solids not fat (SNF) and freezing point for sixty days. Body condition score of individual cows was recorded in a 1-5 scale. Milk samples were collected from individual cow. Samples collected from cows having similar body condition score were mixed together to make composite sample. The results revealed that the body condition score was affected milk yield and fat percentage significantly (P